2017
DOI: 10.1177/2059513117690012
|View full text |Cite
|
Sign up to set email alerts
|

An educational board game for learning and teaching burn care: A preliminary evaluation

Abstract: Timely and effective assessment, resuscitation and transfer of patients with severe burns has been demonstrated to improve outcome. A dedicated one-day course exists to equip all frontline emergency healthcare workers with the necessary knowledge and skills to manage severe burn injuries. More recently, a board game has been developed which aims to act as a learning and practice development tool for those managing burn injuries. We present the findings of our preliminary evaluation of this game. We played this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…GBL is an effective form of instruction to improve the learning achievement of elementary school students (Hobbs & Yan, 2008), middle school students (Giannakos, 2013), high school students (Papastergiou, 2009), and even undergraduate students (Boeker et al, 2013). In terms of board and card games, a previous study found that students who participated in burn game activities achieved the main learning aims, namely increasing their knowledge of burn care and stimulating discussion (Whittam & Chow, 2017). Likewise, a pediatric board game was found to motivate students to advance their knowledge of pediatric medicine (Ogershok & Cottrell, 2004).…”
Section: Effects Of Educational Games On Achievementmentioning
confidence: 99%
“…GBL is an effective form of instruction to improve the learning achievement of elementary school students (Hobbs & Yan, 2008), middle school students (Giannakos, 2013), high school students (Papastergiou, 2009), and even undergraduate students (Boeker et al, 2013). In terms of board and card games, a previous study found that students who participated in burn game activities achieved the main learning aims, namely increasing their knowledge of burn care and stimulating discussion (Whittam & Chow, 2017). Likewise, a pediatric board game was found to motivate students to advance their knowledge of pediatric medicine (Ogershok & Cottrell, 2004).…”
Section: Effects Of Educational Games On Achievementmentioning
confidence: 99%
“…While Berge, Telke, Tate and Trofholz (2019) utilized board game as a tool to observe family functional factors, family interaction, family relationship quality and parenting behaviors during the board games play at home. In addition, educational board games have been used in some areas of medical and health professionals' training and have been shown to enhance learners' knowledge, enjoyment and interest in the subject (Whittam, & Chow, 2017).…”
Section: Social Developmentmentioning
confidence: 99%
“…Some patients with dementia will increase their interest in communicating with others during the games, and tangible props will also increase their hands' flexibility [21]. Whittam et al [22] used a board game called Burns in their research, which contains a folding board. Many question cards are mainly divided into seven categories about pathological knowledge and treatment methods for burn wounds.…”
Section: Development Of Serious Games In Medicalmentioning
confidence: 99%